Impact of domain interchange on conformational stability and equilibrium folding of chimeric class μ glutathione transferases - Luo, Jiann-Kae (Cold Spring Harbor Laboratory Press, 2002)
Rat μ class glutathione transferases M1-1 and M2-2 are homodimers that share a 78% sequence identity but display differences in stability. M1-1 is more stable at the secondary and tertiary structural levels, whereas its quaternary structure is less stable. Each subunit in these proteins consists of two structurally distinct domains with intersubunit contacts occurring between domain 1 of one subunit and domain 2 of the other subunit. The chimeric subunit variants M(12), which has domain 1 of M1 and domain 2 of M2, and its complement M(21), were used to investigate the conformational stability of the chimeric homodimers M(12)-(12) and M(21)-(21) to determine the contribution of each domain toward stability. Exchanging entire domains between class μ GSTs is accommodated by the GST fold. Urea-induced equilibrium unfolding data indicate that whereas the class μ equilibrium unfolding mechanism (i.e., N(2) ↔ 2I ↔ 2U) is not altered, domain exchanges impact significantly on the conformational stability of the native dimers and monomeric folding intermediates. Data for the wild-type and chimeric proteins indicate that the order of stability for the native dimer (N(2)) is M2-2 > M(12)-(12) M1-1 ∼ M(21)-(21), and that the order of stability of the monomeric intermediate (I) is M1 > M2 ∼ M(12) > M(21). Interactions involving Arg 77, which is topologically conserved in GSTs, appear to play an important role in the stability of both the native dimeric and folding monomeric structures.